Pre-9/11 Islamophobia: A Contrapuntal Reading of Don DeLillo’s Falling Man (KEMANUSIAAN The Asian Journal of Humanities, 2024)
Don DeLillo’s Falling Man reproduces the same Orientalist mantra of the Muslim terrorist. Although he is much celebrated for writing thrilling terrorism and assassination novels long before the 9/11 event, many critics situated his Falling Man within the 9/11 neo-Orientalist framework. This study argues that the 9/11 occurrence (while acknowledging its significance) is not the only trigger behind DeLillo’s representation of Muslims in his novel. As such, the study underscores DeLillo’s ideological inclinations by examining his records and the contextual circumstances that transpired before 9/11. By rereading Falling Man, this study situates the investigation within three parameters: the Iranian Revolution, the Rushdie affair and the Clash of Civilisations thesis, thus appropriating the novel within its Islamophobic implicature. Edward Said’s theory of contrapuntal reading, which urges a nonconventional reading of a canonical text, is employed as the theoretical underpinning of this study.